Work Ability, Work Morale, and Work Environment on Employee Performance in Companies Engaged in the Bag Industry: Kemampuan Kerja, Semangat Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan pada Perusahaan yang Bergerak pada Bidang Industri Tas - Ilmi, Ica Safaatul; Sumartik, Sumartik (Universitas Muhammadiyah Sidoarjo, 2023)
The following research is to describe and analyze more deeply the influence of Work Ability, Work Spirit, and Work Environment Variables on an Employee Performance at UD. Suwarlandono Art Tanggulangin. In this research method using a quantitative method, for data collection by using questionnaires. In the sample using a saturated sample, where there are 170 respondents at UD. Suwarlandono Art Tanggulangin. There is an analysis that includes the first classical assumption, the second multiple linear regression analysis, and finally the simultaneous test and also the partial test with the help of a software, namely SPSS version at 22. Then the primary data is obtained through a questionnaire on the measurement, namely by using a scale interval to be tested on the validity and reliability of a data declared valid and reliable. From the results of this study, it proves that work ability, worrk enthusiasm, and worrk environment have a partial and simultaneous influence on emploeyee performance.